Caregiver substance use among families in the U.S. child welfare system: national prevalence estimates - Yoon, Susan; Stanek, Charis; Benavides, Juan Lorenzo; Napier, Taylor; Chang, Yujeong; Nho, Choong Rai (Frontiers in Psychiatry, 2025)
IntroductionUnderstanding the prevalence of caregiver substance use among families affected by the child welfare system can inform prevention and intervention efforts to reduce co-occurring caregiver substance use and child maltreatment. This study examined the national prevalence estimates of alcohol and drug dependence among caregivers affected by the U.S. child welfare system and explored variations based on child and caregiver characteristics.MethodsA secondary data analysis was conducted using the most recent data from the National Survey of Child and Adolescent Well-being (NSCAW-III).ResultsResults indicated that approximately 8% of caregivers met criteria for alcohol dependence and 3% for drug dependence, with about 11% reporting either alcohol or drug dependence. For both alcohol dependence and drug dependence, higher prevalence rates were observed among White caregivers, male caregivers, caregivers of male children, and caregivers who were experiencing domestic violence and/or depression. Distinct patterns emerged in the prevalence rates of alcohol versus drug dependence across caregiver income, education, employment status, and the number of children’s out-of-home placements.DiscussionOur findings highlight nuanced differences between alcohol and drug dependence and point to the need for targeted and contextually responsive programs that address the complex intersection of caregiver substance use and child maltreatment.